Markets and market institutions their origin and evolution - Casson, Mark.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2011)
The origin of markets is a central issue in economics and economic history, but until now there has been no definitive reference source on the subject. This authoritative collection fills the gap by reprinting key papers analysing the evolution of markets over the past millennium. These papers, written by leading scholars in the field, relate market development to urban growth, the spread of the credit system, and the evolution of capitalism. They show that markets did not evolve in a purely spontaneous fashion, but as part of the planned development of market centres by local landowners and business people. This volume, with an original introduction by the editor, will serve as an excellent reference tool to students, academics and practitioners interested in the broad field of economics and economic history, and market evolution in particular.
Amanda McLeod (2008), 'Quality Control: The Origins of the Australian Consumers' Association', Business History, 50 (1), January, 79-98 -- Carol H. Shiue and Wolfgang Keller (2007), 'Markets in China and Europe on the Eve of the Industrial Revolution', American Economic Review, 97 (4), September, 1189-216 -- David S. Jacks (2006), 'What Drove 19th Century Commodity Market Integration?', Explorations in Economic History, 43 (3), July, 383-412 -- Barry K. Goodwin, Thomas J. Grennes and Lee A. Craig (2002), 'Mechanical Refrigeration and the Integration of Perishable Commodity Markets', Explorations in Economic History, 39 (2), April, 154-82 -- S.R. Epstein (1994), 'Regional Fairs, Institutional Innovation, and Economic Growth in Late Medieval Europe', Economic History Review, XLVII (3), August, 459-82 -- James Masschaele (1997), 'The Quest for Markets', in Peasants, Merchants, and Markets: Inland Trade in Medieval England, 1150-1350, Chapter 6, New York, NY: St. Martin's Press, 129-46, 256-8 -- Margaret Spufford (1984), 'Introduction', in The Great Reclothing of Rural England: Petty Chapmen and their Wares in the Seventeenth Century, Chapter 1, London, UK: The Hambledon Press, 1-22 -- R.W. Hoyle (2007), 'New Markets and Fairs in the Yorkshire Dales, 1550-1750', in P.S. Barnwell and Marilyn Palmer (eds), Post-Medieval Landscapes, Chapter 8, Oxford, UK: Windgather Press, 93-106 -- Patrick O'Flanagan (1985), 'Markets and Fairs in Ireland, 1600- 1800: Index of Economic Development and Regional Growth', Journal of Historical Geography, 11 (4), 364-78 -- Ian D. Whyte (1979), 'The Growth of Periodic Market Centres in Scotland 1600-1707', Scottish Geographical Magazine, 95 (1), April, 13-26 -- John R. Walton (1984), 'The Rise of Agricultural Auctioneering in Eighteenth-and Nineteenth-Century Britain', Journal of Historical Geography, 10 (1), 15-36 -- Polly Hill (1966), 'Notes on Traditional Market Authority and Market Periodicity in West Africa', Journal of African History, VII (2), 295-311 -- Ruth Mazo Karras (1989), 'The Regulation of Brothels in Later Medieval England', Signs: Journal of Women in Culture and Society, 14 (2), Winter, 399-433 -- A.J. Arnold and J.M. Bidmead (2008), 'Going "to Paradise by Way of Kensal Green " A Most Unfit Subject for Trading Profit', Business History, 50 (3), May, 328-50 -- Charles R. Mayes (1957), 'The Sale of Peerages in Early Stuart England', Journal of Modern History, 29 (1), March, 21-37
The recommended readings are available in the print version, or may be available via the link to your library's holdings.
Description based on online resource; title from title screen (viewed May 20, 2014).
Keywords: Capital market -- History; Electronic books